Ovarian cyst and pregnancy. What is new? A literature review - Mohsen MA Abdelhafez; Karim AM Ahmed; Mohd NM Daud; Mohamad Saffree Jeffree; Aya AM Eldiastey; Mohd F Bolong; Win W Than; Fairrul Bin Masnah@kadir; Dg Marshitah Pg Baharuddin; Mohd Firdaus Hayati; Nornatherah Azizan; Doreen Sumpat; et al. (Jaypee Brothers Medical Publishers Pvt. Ltd., 2025)
Ovarian cysts with pregnancy constitute a dilemma and challenge in both diagnosis and treatment. This review aims to synthesize, analyze, and accumulate data from published research, particularly the more recent ones, describing the evolving practices in the past 10 years for managing ovarian masses complicating pregnancy. This is a result of the continuous discussion and conundrum surrounding the best course of action for treating adnexal masses in gestation. The frequency of these masses being detected has risen over the past 20 years due to more usage of sonography for pregnancy monitoring. This has also led to technological advancements in screening equipment and a delay in childbearing till later in life. Assembled data from published research, particularly the more recent ones, demonstrating the methods of treating ovarian cysts in pregnancy, have changed over the past 10 years. Most ovarian cysts that form during pregnancy are benign, most likely functional, and have the potential to disappear on their own. Thankfully, most of these tumors are discovered unintentionally during a normal ultrasound scan performed during the initial prenatal visit during the first trimester of pregnancy. Ultrasound is the first choice and recommended diagnostic modality for the preliminary finding and monitoring of ovarian cysts whether in or following pregnancy. When ultrasonography (US) imaging is inconclusive, magnetic resonance imaging (MRI) and computed tomography (CT) scans can be helpful supplements. Conservative, surgical, or ultrasound-guided aspiration of big cysts are all possible treatment options for ovarian cysts during pregnancy.